Evaluation of Smoked Skipjack Processing Byproduct Meal as an Alternative Feed Ingredient for Juvenile Humpback Grouper Cromileptes altivelis - Muhamad Agus Suprayudi; Fatma Hajiali; Nur Bambang Priyo Utomo; Julie Ekasari; Ichsan Fauzi (HAYATI Journal of Biosciences, 2016)
This study aimed to evaluate the utilization of smoked skipjack processing byproduct meal (SPBM) to reduce the use of fish meal (FM) for juvenile humpback grouper Cromileptes altivelis. This study consisted of digestibility test of SPBM and biological test to observe growth performance. Five isonitrogenous and isocaloric experimental diets were used: Diet A contains 0% SPBM as a control diet, and diets B, C, D, and E contain 25%, 50%, 75%, and 100% of SPBM protein to substitute FM, respectively. Digestibility trial was performed for 14 days by adding Cr2O3 into the experimental diets and collecting fecal matter 40–60 minutes after each feeding. For growth trial, juvenile humpback grouper were kept in glass aquariums and fed by the experimental diet until apparent satiation for 60 days. Our result shows that the dry matter and protein SPBM apparent digestibility coefficient is lower compared to FM. The fish that was fed with diet B and C performed a comparable specific growth rate, feed efficiency, and protein retention compared to control (p > 0.05). However, lower specific growth rate, feeding efficiency, and protein retention were observed in fish that was fed with diet D (75% SPBM) and diet E (100% SPBM; p < 0.05). These results indicate that up to 50% of smoked SPBM can be used for the diet of humpback grouper.